Diagnosis of Primary Trimethylaminuria in an Affected Patient With a Rare Genotype in Sub‐Saharan Africa - M. Dercksen; M. Perumal; E. Davoren; D. R. Reed; C. Murry‐Maritz; R. van derSluis; S. Mason (JIMD Reports)
ABSTRACT Primary trimethylaminuria (TMAU) is characterized by systemic accumulation of trimethylamine (TMA) due to the deficient activity of flavin‐containing monooxygenase 3 (FMO3). The disorder does not have detrimental pathophysiological consequences, but patients develop psychological symptoms due to the emotionally debilitating bodily odor defined as decaying fish that affects their quality of life. Here, we illustrate the utility of a diagnostic workup on an adolescent with primary TMAU, including biochemical and genetic investigations that confirm the diagnosis. A direct substrate (TMA) loading protocol was used, followed by the collection of urine samples at predetermined intervals. The conversion of TMA to trimethylamine oxide (TMAO), monitored by 1H‐NMR spectrometry, showed a compromised FMO3 metabolic capacity at baseline, becoming more pronounced after loading commenced. The eight coding exons of the FMO3 gene were Sanger sequenced, revealing a homozygous missense variant, c.23T>C (p.Ile8Thr), as well as two known homozygous variants, c.472G>A (p.Glu158Lys) and c.923A>G (pGlu308Gly), associated with no to mild presentation of TMAU. The advantage of direct substrate‐to‐product monitoring is the elimination of alternative contributors to the odor that would result in the diagnosis of secondary TMAU. The combined functional and genetic approach provided adequate evidence to describe the first primary TMAU patient reported in sub‐Saharan Africa with a genotype not yet described in a homozygous state. Our findings motivate a comprehensive biochemical and genetic approach to discriminate between primary and secondary TMAU. Subsequently, this targeted approach can provide advice on therapeutic management for optimal emotional well‐being.